تبدلات الكتلة العظمية عند مرضى الديلزة - حسن, عبد الرزاق; سعيد, حسين; خليلو, لؤي (Latakia University Journal -Medical Sciences Series, 2019)
من أجل استقصاء التغيرات في الكتلة العظمية ]كثافة المركبات المعدنية للعظم (BMD )[ عند مرضى الديلزة, تمت دراسة الكتلة العظميـة عنـد (53) مريضاً من قسم الديلزة في مشفى الأسد الجامعي في اللاذقية, وقد كانوا جميعهم مصـابين بقصور كلوي نهائي, ومعالجين بالديلزة الدموية الدورية. تبين نتيجة الدراسة وجود علاقة سلبية واضحة بين الكثافة العظمية ( BMD ) وكل من: عمر المريض, الجنـس الأنثوي ومستوى هرمون الدريقات المصلي. في حين كانت العلاقة الإيجابية واضحـة بين BMD وكل من: تركيز الخضاب, جرعة [α-1-OH-D3] (ون-ألفا)الأسبوعية وجرعة الكالسيوم التعويضية. في حين أن العلاقة لم تكن واضحة تماماً بين الـ BMD وجرعة الهيبارين الأسبوعية وبإيجاد عامل الارتباط (R) إحصائياً بين كل العوامل السابقة وBMD كانت النتائج مطابقة لنتائج الدراسـة التجريبية. In order to investigate the changes in the bone mass in the hemodialysis patients, the bone mass has been studied in 53 patients of in the Hemodialysis Section at AL-Assad University Hospital in Lattakia. All patients were suffering from final renal deficiency and under treatment for periodic hemodialysis. The result of this study has shown the existence of a clear negative relation between the BMD and each of the patients' age, the female gender, and the level of the serum parathyroid hormone (PTH); while there has been a clear positive relation between the BMD and each of the hemoglobin concentration, the weekly one- Alpha dose and the weekly Heparin dose. By finding the Relation Coefficient (R) statistically between all the above factors and BMD, all the results came conformable to the experimental study results.